2013
DOI: 10.1177/0021998313489899
|View full text |Cite
|
Sign up to set email alerts
|

Properties of wood plastic composite panels made from waste sanding dusts and nanoclay

Abstract: This article presents the application of waste sanding dusts in order to evaluate its suitability as reinforcement for thermoplastics as an alternative to wood fibers. The effects of sanding dust loading and nanoclay content on the physical and mechanical properties were also studied. Overall trend showed that with addition of sanding dusts, tensile and flexural properties of the composites were significantly decreased, due to the reduction of interface bond between the fiber and matrix. It was found that flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
2
20
0
1
Order By: Relevance
“…Madhoushi et al (2014) uptake and thickness swelling were significantly reduced due to OMt occupying some voids of the composites. Besides, owing to the improved interfacial bonding between WF and polymer matrix, the mechanical properties of the composites increased a lot (Zahedi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Madhoushi et al (2014) uptake and thickness swelling were significantly reduced due to OMt occupying some voids of the composites. Besides, owing to the improved interfacial bonding between WF and polymer matrix, the mechanical properties of the composites increased a lot (Zahedi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Wood–plastic composites (WPCs) have been introduced successfully to the academic sectors due to considerable processing advantages and improvement in certain physical and mechanical properties during the previous decades . Materials now known as WPCs first appeared in the 1960s .…”
Section: Introductionmentioning
confidence: 99%
“…Materials now known as WPCs first appeared in the 1960s . For making WPCs, the lignocellulosic fibers may be obtained from wood species or agro‐based fibers . Currently, most WPC is for use in exterior building component and building panels, including decking, roofline products, windowsills, flooring material for trucks, standard containers, playground equipment, fencing, industrial flooring, landscape timbers, and railing .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the composites with a high fraction of RNF had high water absorption. Madhoushi et al 18 studied the effects of sanding dust loading and nanoclay content on the physical and mechanical properties of polypropylene. Addition of sanding dust significantly decreased tensile and flexural properties of the composites, and flexural, tensile, and withdrawal strength of fasteners were improved by the addition of 2 wt% nanoclay in the matrix.…”
Section: Introductionmentioning
confidence: 99%